The role of gyrA and parC mutations in fluoroquinolones-resistant Pseudomonas aeruginosa isolates from Iran - Nouri,Roghayeh (2016)
Abstract The aim of this study was to examine mutations in the quinolone-resistance-determining region (QRDR) of gyrA and parC genes in Pseudomonas aeruginosa isolates. A total of 100 clinical P. aeruginosa isolates were collected from different university-affiliated hospitals in Tabriz, Iran. Minimum inhibitory concentrations (MICs) of ciprofloxacin and levofloxacin were evaluated by agar dilution assay. DNA sequences of the QRDR of gyrA and parC were determined by the dideoxy chain termination method. Of the total 100 isolates, 64 were resistant to ciprofloxacin. No amino acid alterations were detected in gyrA or parC genes of the ciprofloxacin susceptible or ciprofloxacin intermediate isolates. Thr-83 → Ile substitution in gyrA was found in all 64 ciprofloxacin resistant isolates. Forty-four (68.75%) of them had additional substitution in parC. A correlation was found between the number of the amino acid alterations in the QRDR of gyrA and parC and the level of ciprofloxacin and levofloxacin resistance of the P. aeruginosa isolates. Ala-88 → Pro alteration in parC was generally found in high level ciprofloxacin resistant isolates, which were suggested to be responsible for fluoroquinolone resistance. These findings showed that in P. aeruginosa, gyrA was the primary target for fluoroquinolone and additional mutation in parC led to highly resistant isolates.